Identification of causative pathogen and its antibiotic sensitivity in cases of preterm premature rupture of membranes - Kandukuri, Sai Prasanna; Chadalawada, Ramamani; Gollapalli, Bhavishya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pre-labor rupture of membranes is defined as amniotic membrane rupture before the onset of labor contractions, and if it happens before 37 weeks, it is called preterm premature rupture of membranes (PPROM). Several organisms commonly present in the vaginal tract are E.coli, Group-B streptococci, staphylococcus aureus, chlamydia trachomatis, Gardnerella vaginalis and Enterococcus faecalis which secrete proteases that degrade collagen thereby weakening the fetal membranes leading to PPROM. Appropriate antibiotic therapy has a significant role in the prevention and treatment of maternal and neonatal complications. Methods: This was a prospective observational study done in the department of obstetrics and gynaecology, Narayana medical college, Nellore. Selectively 100 patients with complaint of PPROM admitted to labor room were included in the study. Diagnosis of membrane rupture was established by speculum examination, and high vaginal swabs are taken and sent to laboratory for identifying bacteria using gram staining and cultured in aerobic and anaerobic methods. Antimicrobial susceptibility testing of the organisms was performed by disk diffusion method by Kirby and Bauer. Results: Out of 100, high vaginal swabs had growth in 82 patients, and 18 were sterile. The repeatedly isolated organism in patients with PPROM is E.coli amounting 32%, followed by candidal species 20%. Staphylococci are scoring 11% and enterococci 8%. However, organisms like gardenella vaginalis and Group B streptococcus are least common with a score of 6% and 5% respectively. In this study, E.coli is highly sensitive to tigecycline, colistin 100% each and highly resistant to gentamycin and amikacin. Conclusions: In this study, E.coli is related to the maximum number of cases with preterm premature rupture of membranes. Appropriate use of antibiotics significantly lowers maternal morbidity and neonatal mortality.